Impact of technological, organizational, environmental, use of E-marketing, technological opportunism on performance of Pakistan textile sector - Sheikh, Adnan Ahmed (2018)
Today, the effective use of technological revolution and innovations arc arguably one of the key challenges confronted by the textile industry in Pakistan. Therefore to understand diverse perspectives of technology diffusion and textile sector performance, the study examines the effect of technological factors which are relative advantage (RA), technology orientation (TO). organizational factors which are market orientation (MO), organization resources (OR), top management support (TMS) and environmental factors which are competitive pressure (CP), pressure from trading partners (TP) and government support (GS) on the textile firms performance (FP) in Pakistan through the mediating role of use of e-marketing (UFM) and moderating effect of technological opportunism (TOP) between UEM and FP. The study framework was established from theories, namely the Resource Based View, the Diffusion of Innovation and the Technology-Organization-Environment framework. Data was collected from general manager marketing working in textile manufacturing firms of Pakistan. Out or the 480 distributed questionnaires, 257 were returned. The cluster proportionate sampling technique was used. Hypotheses tests were performed on SmartPLS SEM 3.0. The results show that RA, TO. TMS, CP and TP have significant direct relationship with UEM and FP. Whereas, OR, MO found insignificant with UEM and FP but GS found significant with FP only. The use of e-marketing as a mediating variable played a significant role between TO, RA, MO, TMS, TP, CP and FP. except OR and GS. The findings also confirmed that technological opportunism (TOP) moderated the relationship between UEM and FP. However, the outcomes of this study have key contribution for the marketing field, as it strain the vital role of marketing persons in the effective implementation of e-marketing and its antecedents and also by filling the gap in the literature to enhance overall textile sector performance. Lastly, future research should include other innovative variables and theories to check the validity of model in different industries and countries.